Thromboxane Modulates Endothelial Permeability - J. M. Klausner; S. Abu-Abid; J. S. Alexander; R. Hanshke-Mineau; G. Goldman; N. Morel; C. R. Valeri; D. Shepro; H. B. Hechtman (Hindawi Limited, 1994)
The study tests the role of thromboxane in modulating microvascular permeability in vitro. Cultured monolayers of bovine aortic endothelial cells were challenged with the thromboxane (Tx) mimic U46619. This led to disassembly of actin microfilaments, cell rounding, border retraction and interendotheHal gap formation. Pretreatment with the Tx receptor antagonist SQ 29,548 prevented the Tx mimic-induced cytoskeletal changes. The Tx mimic also altered endothelial cell barrier function. Increased permeability was indicated by the increased passage of labelled albumin across monolayers cultured on microcarriers, relative to untreated endothelial cells (p<0.05). Furthermore, electron microscopy of endothelial cells cultured on the basement membrane of human placental amnion indicated increased permeability based on wide, interendotheHal gap formation and transit of the tracer horseradish peroxidase. Quantification of interendothelial gaps revealed an eleven-fold increase with the Tx mimic relative to untreated endothial cells (p<0.05) and prevention by pretreatment with the Tx receptor antagonist (p<0.05). These data indicate that Tx directly modulates the permeability of endothelial cell in vitro.